Peran Pinjaman Dana Berbasis Online Melalui Aplikasi Media Massa Terhadap Komunikasi Bisnis Untuk Perekonomian Di Indonesia - Devi safitri; Putra Rizky Gustianda; Ria Anjriani Saputri; Widyani hasibuan; Suhairi (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
One of the facilities offered by Indonesian financial institutions is credit. Where in Indonesia, the demand for credit is very high. To support this, online loans have appeared which have an important role as a partner of the government which will contribute to channeling more loans to customers. The role of online loans through applications with various advantages which include: fast process; easy terms; flexible; credit calculators; as well as a variety of products, it is hoped that this will help equalize the public to become users of financial services. With affordable access to finance for all levels of society, of course it can help move the Indonesian economy and make a major contribution to the progress of economic development, especially in Indonesia.